Platelets stimulate programmed death‐ligand 1 expression by cancer cells: Inhibition by anti‐platelet drugs. (8th August 2021) - Asgari, Amir; Lesyk, Gabriela; Poitras, Erika; Govindasamy, Natasha; Terry, Kara; To, Rachel; Back, Valentina; Rudzinski, Jan K.; Lewis, John D.; Jurasz, Paul
Abstract: Background: Platelets facilitate hematogenous metastasis in part by promoting cancer cell immunoevasion, although our understanding of platelet function in modulating the adaptive immune system in cancer is limited. A major negative regulator of the adaptive response is the immune checkpoint protein Programmed Death Ligand 1 (PD‐L1). Objectives: As platelets secrete factors that may increase PD‐L1 expression, we investigated whether they up‐regulate cancer cell PD‐L1, thus promoting immunoevasion, and whether common anti‐platelet drugs inhibit this process. Methods: Platelets were isolated from human volunteers. A549 lung, PD‐L1 null A549, and 786‐O renal cancer cells were incubated with and without platelets, and cancer cell PD‐L1 expression was measured by qPCR and flow cytometry. Additionally, platelet‐cancer cell incubations were performed in the presence of common anti‐platelet drugs, and with growth factor neutralizing antibodies. Following incubation with platelets, A549 were co‐cultured with T‐cells and interleukin‐2 (IL‐2) levels were measured by flow cytometry as a marker of T‐cell activation. Results: Platelets increased PD‐L1 mRNA and surface protein expression by A549 and 786–0 cells. Combined neutralization of VEGF and PDGF prevented the platelet‐induced up‐regulation of PD‐L1 by A549, as did the anti‐platelet drug eptifibatide. A549 incubated with platelets demonstrated a reduced ability to activate human T‐cells, an effect reversed by eptifibatide. Conclusions: As platelets promote immunoevasion of the adaptive immune response by increasing cancer cell PD‐L1 expression and as anti‐platelet drugs prevent this immunoevasive response, the investigation of anti‐platelet drugs as adjuvant therapy to immune checkpoint inhibitors may be warranted in the treatment of cancer.